The effect of hypericum perforatum on kidney ischemia/reperfusion damage. (1st January 2017) - Cakir, Murat; Duzova, Halil; Baysal, Işil; Gül, Cemile Ceren; Kuşcu, Gülbahar; Kutluk, Fatma; Çakin, Hilal; Şeker, Şifanur; İlbeği, Esranur; Uslu, Seda; Avci, Umut; Demir, Samet; et al.
Abstract: It has been revealed in recent studies that Hypericum Perforatum (HP) is influential on cancer, inflammatory diseases, bacterial and viral diseases, and has neuroprotective and antioxidant properties. In this study, we investigated the effect of HP, which is known to have antioxidant and anti-inflammatory effects, on kidney I/R damage. Male Sprague–Dawley rats were divided into three groups, and each of the groups had eight rats: The Control Group; the Ischemia/Reperfusion (I/R) Group; and the IR + HP Group which was treated with 50 mg/kg of HP. The right kidneys of the rats were removed, and the left kidney developed ischemia during the 45th min, and reperfusion occurred in the following 3rd h. The histopathological findings and also the level of Malondialdehyde (MDA), Glutathione (GSH) and superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-PX) enzyme activations in the renal tissues were measured. Blood Urea Nitrogen (BUN), Creatinin (Cre) from serum samples were determined. The levels of BUN, Cre, and kidney tissue MDA increased at a significant level, and the SOD, CAT, and GSH-PX enzyme activity decreased at a significant level in the I/R group, compared with the Control Group ( p  < 0.05). In the I/R + HP group, the levels of MDA decreased at a significant level compared to the I/R group, while the SOD, CAT, and GSH-PX activity increased ( p  < 0.05). In histopathological examinations, it was observed that the tubular dilatation and epithelial desquamation regressed in the IR + HP Group when compared with the I/R Group. It has been shown with the histological and biochemical results in this study that HP is protective against acute renal I/R.